After the Boats Stopped: Refugees Managing a Life of Protracted Limbo in Indonesia - Thomas Brown (Antropologi Indonesia, 2017)
In 2013, Australia enacted tough border policies to “stop the boats”, leaving Indonesia to play host to a burgeoning number of refugees who now spend years, rather than months in the country, awaiting resettlement through the UNHCR to a third country. In Indonesia, asylum seekers live in a state of limbo and are deprived of access to education and employment. Given the uncertainty and increasing length of stay, the question emerges: how do people manage their lives in response to this protracted, yet impermanent, situation? In particular, how do refugees build relations with one another and with their Indonesian hosts? In West Java, Hazara refugees from Afghanistan respond to their uncertain situation by forming a strong co-ethnic community to navigate their new environment. Even though these urban refugees live in and amongst Indonesian host communities, they have little meaningful interaction with Indonesians and demonstrate very little uptake of the language, behaviours or cultural practices of their neighbours. This phenomenon of forming a community within, but at the same time apart from the host community is demonstrated with primary data collected over a six-week period in West Java using a combination of participant observation and interview methods. Based on comparison with other urban refugee contexts and ethnic Hazara diaspora groups, it is argued that the extent to which refugees form bonds with the local population is dependent on structural factors, in particular the formal and informal legal framework for refugees, access to education and employment, cultural and linguistic differences, and discrimination.Keywords: Refugees, Asylum Seekers, Acculturation, Hazara